Pengaruh kesepian terhadap presentasi diri online pada dewasa awal pengguna instagram - Assyfikqi, Rahardian Puji; Prasetyaningrum, Susanti; Hijrianti, Udi Rosida (Cognicia, 2024)
Emerging adulthood can show self-expression and communicate with others via Instagram, especially by sharing photos and videos. When presenting themselves on the internet, individuals must have the ability to create a good impression virtually. A survey conducted by the Mental Health Foundation shows that people aged 18 to 34 experience loneliness more often because the expected need for intimacy from close people is not met, a gap is created between expectations and the reality of formed social relationships, and a lack of satisfaction from social relationships which exists. The aim of this research is to determine the influence of loneliness on online self-presentation in early adult Instagram users. The research method used was quantitative with single regression analysis, and to distribute the research sample using convenience sampling techniques to obtain 162 respondents who had the criteria of being 18-27 years old, actively using Instagram. The instrument used refers to the theory of loneliness and online self-presentation, and produces a significance value of 0,001 (p<0,05) which can be explained if the hypothesis that there is an influence of loneliness on online self-presentation is accepted with an effective contribution of 7,9%.